Value Creation Opportunities of Generative AI – A Case Study (Junior Management Science, 2025)
The transformative potential of Generative AI promises novel capabilities within business environments. This study examines the value creation potential of Generative AI within a large multinational corporation. A single case study approach at Siemens was employed, combining extensive observations, interviews, and the application of existing AI frameworks. Findings reveal diverse use cases demonstrating value creation potential, particularly through smart assistants and lighthouse projects. This thesis proposes a novel framework for Generative AI adoption, emphasizing the distinctive exploration phase made possible by the technology’s accessibility to non-technical domain experts, while also outlining essential scaling strategies. This study offers valuable insights into a company’s approach to Generative AI, provides practical implications, and expands ongoing research on AI-driven value creation.Keywords: artificial intelligence; exploration; generative AI; scaling; technology adoption; use cases; value creation